Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar Siswa Kelas X IPS E di SMA Negeri 10 Medan pada Materi Penelitian Geografi - Vina Aulia; Shika Andari; Khairun Nisa (Universitas Palangka Raya, 2025)
This research aims to explore the application of the Problem Based Learning (PBL) Model in an effort to improve the learning outcomes of class X IPS E students at SMA Negeri 10 Medan, especially in geographic research material. The background to this research is revealed by the low learning achievement of students, where only 40% of them achieved the Minimum Completeness Criteria (KKM). PBL was chosen as an approach because this method can encourage students to actively participate in the learning process through solving real problems, which is expected to improve their critical thinking skills and conceptual understanding. This research methodology involves systematic planning, data collection through observations and tests, and comprehensive data analysis. The research results show that the implementation of PBL significantly improves student learning outcomes. In the first cycle, there was an increase in understanding of concepts and evaluation values, which further developed in the second cycle with better results. This research concludes that PBL is effective in improving student learning outcomes in geography material and recommends teachers to apply innovative learning methods in the teaching and learning process.